Proceedings of the 1st International Conference on Energy-Efficient Computing and Networking 2010
DOI: 10.1145/1791314.1791325
|View full text |Cite
|
Sign up to set email alerts
|

Mobile networks unplugged

Abstract: Mobile network access has seemingly become ubiquitous in industrialized countries. With data services becoming sufficiently fast, usable, and affordable, demand is growing rapidly, both in the number of users and in capacity -since most Internet/web resources continue being tailored for fast fixed line access. A lot of engineering has gone into making mobile devices appealing and sufficiently power-conserving to last for at least a day in spite of the many emerging network-driven applications. However, this de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Even though every new generation of mobile networks brought a decrease of the energy consumption per bit of data, the total power consumption of base stations increases with their total throughput capacity (Manner et al ). This, together with higher bandwidth usage by mobile services (Cisco Newsroom ), means their relevance will grow.…”
Section: Discussionmentioning
confidence: 99%
“…Even though every new generation of mobile networks brought a decrease of the energy consumption per bit of data, the total power consumption of base stations increases with their total throughput capacity (Manner et al ). This, together with higher bandwidth usage by mobile services (Cisco Newsroom ), means their relevance will grow.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the performance was insensitive to the mode holding time within a certain range. In [55], a practical implementation for approximating an energy-proportional (EP) 3G system by using non-EP BS components to cope with temporalspatial traffic dynamics was presented. The article also proposed that the under-utilized BSs would be shut down and restarted again as needed.…”
Section: Figure 5 Impact On Energy Consumption Of Different Stages Of...mentioning
confidence: 99%
“…The explosive demand for high data rate of mobile users has caused BSs to be the dominant total energy consumer within the cellular networks. It has been shown that the energy consumption for an LTE network has to increase about 60 times compared to a 2G network to offer the same level of coverage [115]. Due to this, most studies on EE in mobile cellular radio networks focused on the BS side.…”
Section: Bs's Energy-awarenessmentioning
confidence: 99%